Clinical and psychological analysis of states of psychological maladaptation in servicemen of the State Border Guard Service of Ukraine - Cherniaiev Михайло (Psychosomatic Medicine and General Practice, 2019)
The goal of the work. The purpose of the work is to carry out a clinical and psychological analysis of the states of psychological maladaptation in the servicemen of the State Border Guard Service of Ukraine who took part in the hostilities. Contingent and research methods. With informed consent, 159 servicemen (VS) of the State Border Guard Service of Ukraine (SBU) who took part in hostilities were examined at the Hospital of the State Border Guard Service of Ukraine. The comprehensive examination included the use of clinical-psychological and psychodiagnostic methods. Results of the research. Of the total number of 103 respondents (64.7%) found outlined signs of psychological maladaptation (PDA) of varying intensity (main group, CO), 56 people (35.3%) - single individual signs of PDA (comparison group, GP). 69 people (43.4%) with symptoms of PDA were included in the CO, which, according to the authors of the method, we interpreted as manifestations of neuroticism with a high level of psycho-emotional tension, and 34 people (21.4%), in whom the presence of outlined maladaptive symptoms, often, syndromic design. The GP, respectively, included 52 respondents (32.7%) who had some isolated signs of PDA, which indicated the pre-nosological severity and immaturity of its symptoms, and 4 people (2.5%) with no existing signs of PDA. In the course of the work, a wide range of pathopsychological and negative socio-psychological phenomena associated with PDA in the Armed Forces of the State Tax Service of Ukraine, which took part in hostilities, was established. Among the main manifestations - the presence of affective disorders of mild depression (subdepression), comorbid manifestations of addictive behavior at the level of risky or harmful use of alcohol, tobacco, coffee (tea), cannabinoids, sedatives and stimulants, overeating, watching TV, computer use, computer, and gambling, as well as reducing the level of general socio-psychological adaptation and quality of life. Conclusion. The identified patterns should be taken into account in the development of treatment-and-rehabilitation and preventive measures for the Armed Forces of the State Tax Service of Ukraine, which took part in hostilities.